PENGEMBANGAN TEKNIK RELAKSASI NAPAS DALAM KOMBINASI GERAK TANGAN UNTUK MENSTABILKAN TEKANAN DARAH PENDERITA HIPERTENSI - Nina Yuliani; Mujito - -; Triana Setijaningsih; Tri Cahyo Sepdianto (Poltekkes Kemenkes Malang, 2021)
Hypertension is the third largest risk factor that causes premature death. Deep breathing relaxation technique is a non pharmacological therapy that can be introduced to hypertensive clients. Deep breathing relaxation can make the body harmonious and calm and can empower the body to fight hypertension. The development of breath relaxation techniques in combination with hand movements is expected to maintain blood pressure stability in hypertensive clients. The purpose of this study is to identify the process of developing and the feasibility of breathing relaxation techniques in combination with hand movements to stabilize the blood pressure of hypertensive clients. The method used in this research is Research and Development with ADDIE development procedures up to the implementation stage, namely making the final product. This research was conducted in Posbindu PTM of Bendogerit Sub District, Blitar City with 8 trial participants. The results of this study indicate that breath relaxation techniques in combination with hand gestures meet the appropriate criteria for use based on expert judgment and trial participants. The creation of the final product is expected to be the next researcher to conduct research on the effectiveness of this product to maintain blood pressure stability in hypertensive clients